Pengaruh Edukasi Upaya Pencegahan Demam Berdarah melalui Flashcard terhadap Tingkat Pengetahuan Siswa Sekolah Dasar - Kustati Budi Lestari; Noni Tasya; Dwi Setyowati; ratna Pelawati (Pusat Riset dan Inovasi Nasional, 2025)
Dengue fever continues to pose a serious threat to global public health, particularly among children aged 5 to 14 years. Schools are potential hotspots for the transmission of dengue hemorrhagic fever due to students' limited knowledge regarding its transmission and prevention. Educational interventions using engaging media, such as flashcards, are considered effective in enhancing awareness and preventive behaviors. Objective: This study aimed to examine the effect of flashcard-based education on elementary school students' knowledge of dengue fever prevention. Methods: A quasi-experimental design with a nonequivalent control group was employed. The study involved 30 students from grades 5 and 6 at SDN 1 Sajira, who were divided equally into intervention and control groups. The intervention group received health education using flashcards. Data were analyzed using paired t-tests and independent t-tests to evaluate the effectiveness of the intervention. Results: The bivariate analysis showed a statistically significant increase in the knowledge scores of students in the intervention group (p-value = 0.000; p < 0.05). This indicates that the flashcard-based education had a significant positive effect on students' knowledge regarding dengue prevention. Conclusion: Flashcard-based health education is effective in increasing knowledge about dengue prevention among elementary school students. Schools are encouraged to implement similar educational strategies and collaborate with local health centers to support dengue eradication efforts.